Imagining the possibilities of a cross-cultural oral narrative portraiture method: stepping beyond binary discourses - Weuffen, Sara; Pickford, Aunty Marjorie (The Australian Journal of Indigenous Education, 2019)
Abstract Contemporary scholarly critique in Indigenous research spaces has tended to focus on binary dualities, including the purpose of Indigenous-focused research, and the legitimacy of researcher identity, research knowledge and truth. Yet, perhaps unintentionally, such interrogation has led to the continued (re)construction and maintenance of false race-based dichotomies. In this paper, one way in which we seek to step beyond binary race-based discourses is by advocating for the advancement of cross-cultural research practices that interweave traditional and contemporary communication practices. We put forward the case that by knitting together Eurocentric and Indigenous research methodologies, Lawrence-Lightfoot's (2005, Qualitative Inquiry 11, 3–15) portraiture method, and Aboriginal practices of storytelling/yarning, the cross-cultural oral narrative portraiture method enables co-construction of more holistic, culturally nuanced and responsive stories, where meaning, context and reason resonate. In the 21st century research space, we open dialogue for thinking about data as stories, and advocate for contemporary intercultural research processes that are inclusive, engaging and promote co-construction of narratives for storying.